Gait Analysis in Progressive Supranuclear Palsy Phenotypes - Picillo, Marina; Ricciardi, Carlo; Tepedino, Maria Francesca; Abate, Filomena; Cuoco, Sofia; Carotenuto, Immacolata; Erro, Roberto; Ricciardelli, Gianluca; Russo, Michela; Cesarelli, Mario; Barone, Paolo; Amboni, Marianna (Frontiers in Neurology, 2021)
Objective of the present study was to describe gait parameters of Progressive Supranuclear Palsy (PSP) phenotypes at early stage verifying the ability of gait analysis in discriminating between disease phenotypes and between the other variant syndromes of PSP (vPSP) and Parkinson’s disease (PD). Nineteen PSP (10 PSP-Richardson's syndrome, 5 PSP-parkinsonism and 4 PSP-progressive gait freezing) and 9 PD patients performed gait analysis in single and dual task. Although phenotypes showed similar demographic and clinical variables, Richardson’s syndrome presented worse cognitive functions. Gait analysis demonstrated worse parameters in Richardson’s syndrome compared to the other variant syndromes of PSP. The overall diagnostic accuracy of the statistical model during dual task was almost 90%. Correlation analysis showed a significant relationship between gait parameters and visuo-spatial, praxic and attention abilities in PSP-Richardson’s syndrome only. vPSP presented worse gait parameters compared to PD. Richardson’s syndrome presents greater gait dynamic instability since the earliest stages compared to other phenotypes. Computerized gait analysis can differentiate between PSP phenotypes and between vPSP and PD.